STEM CELL THERAPIES IN INDIA - Karuvelil, John (Asian Horizons, 2013)
The successful completion of the Human Genome Project has helped the medical/pharmaceutical field the most. The knowledge received from the findings of this project has engaged equally researchers, medical professionals, pharmaceutical companies and governments.1 While many governments allocate huge funds into stem cell research aimed at development of medicines with the hope of finding cures for diseases that have eluded lasting cures through conventional medicines or treatments, pharmaceutical companies invest heavily into the field with the hope of making huge profits.